VDC in Practice: A Preliminary Categorization of Production Metrics reported in Scandinavia and Latin America - Majumdar, Tulika (2022)
Architecture, Engineering and Construction (AEC) teams are increasingly using emerging management methods involving collaboration, lean construction, and digitization for managing projects. Production metrics (PM) are being used to assess the impact of these methods on project performance during run-time. A lack of common vocabulary hinders comparison of PM, making it difficult to repeat strategies used for improving project performance and for benchmarking PM across projects. Through a detailed content analysis, 2 datasets of 904 PM reported by 195 Virtual Design and Construction (VDC) practitioners in Scandinavia and Latin America were curated. Qualitative coding was used to categorize the PM into the three key VDC elements, i.e., Integrated Concurrent Engineering (ICE), Building Information Modeling (BIM) and Project Production Management (PPM) and to validate the categorization. This research enabled a comparison of PM categories across the two regions for the first time. PM categorized as ICE and PPM were reported by more than 68% professionals in both the regions. BIM PM had a disparity in reporting (Scandinavia: 30%, Latin America: 91%). It also opened a pathway to develop a common vocabulary of PM to compare, benchmark and standardize PM across VDC implementations.